2016
DOI: 10.1098/rstb.2016.0019
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory modulation of startle eye blink: a new approach to assess afferent signals from the respiratory system

Abstract: One contribution of 16 to a theme issue 'Interoception beyond homeostasis: affect, cognition and mental health'. Current approaches to assess interoception of respiratory functions cannot differentiate between the physiological basis of interoception, i.e. visceralafferent signal processing, and the psychological process of attention focusing. Furthermore, they typically involve invasive procedures, e.g. induction of respiratory occlusions or the inhalation of CO 2 -enriched air. The aim of this study was to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…It is known that a considerable portion of HRV variance is explained by state-specific factors (Bertsch, Hagemann, Naumann, Sch€ achinger, & Schulz, 2012). Moreover, several other mechanisms not explored by our manipulation, such as respiratory activity (Eckberg, 2003;Schulz, Schilling, V€ ogele, Larra, & Sch€ achinger, 2016), are also important contributors to beat-to-beat changes in heart rate. On the other hand, the lack of significant HRV effects may reflect type-II error inherent to single HRV measurements with relatively small sample size (Bertsch et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…It is known that a considerable portion of HRV variance is explained by state-specific factors (Bertsch, Hagemann, Naumann, Sch€ achinger, & Schulz, 2012). Moreover, several other mechanisms not explored by our manipulation, such as respiratory activity (Eckberg, 2003;Schulz, Schilling, V€ ogele, Larra, & Sch€ achinger, 2016), are also important contributors to beat-to-beat changes in heart rate. On the other hand, the lack of significant HRV effects may reflect type-II error inherent to single HRV measurements with relatively small sample size (Bertsch et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Schulz et al [42] have previously shown that the eyeblink startle is modulated by interoceptive cardiac afferent signals. Here, the authors focus on the respiratory system and for the first time present startle modulation by respiration.…”
Section: Measuring and Modulating Interoceptionmentioning
confidence: 99%
“…Indeed, studies of respiration-brain coupling have recently attracted increased attention, reporting a range of cognitive and motor processes to be influenced by respiration phase. Human participants were found to spontaneously inhale at onsets of cognitive tasks 6 and respiration phase modulated neural responses in sensory 7 and face processing 8 tasks as well as during oculomotor control 9 . Parallel to this body of work, animal studies have conclusively shown respiration to entrain brain oscillations not only in olfactory regions 10 , but also in rodent whisker barrel cortex 11 and even hippocampus 12 .…”
Section: Introductionmentioning
confidence: 99%